2014
DOI: 10.3389/fpsyg.2014.01147
|View full text |Cite
|
Sign up to set email alerts
|

Learning and processing of nonverbal symbolic information in bilinguals and monolinguals

Abstract: Bilinguals have been shown to outperform monolinguals on word learning and on inhibition tasks that require competition resolution. Yet the scope of such bilingual advantages remains underspecified. We compared bilinguals and monolinguals on nonverbal symbolic learning and on competition resolution while processing newly-learned material. Participants were trained on 12 tone-to-symbol mappings, combining timbre, pitch, and duration of tones. During subsequent processing, participants viewed a display with four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 100 publications
2
5
0
Order By: Relevance
“…Their results imply that (at least part of) the multilingual advantage is rooted in better access to the recently learned words because the training procedure ensured the same level of learning across groups. A similar pattern emerged in a recent study by Blumenfeld and Adams (2014). In that study, no difference was observed between Spanish-English bilinguals and English monolinguals on a nonverbal sound-to-symbol mapping task, which required mapping of tones to symbols based on pitch, timbre, and duration.…”
Section: Adultssupporting
confidence: 83%
See 2 more Smart Citations
“…Their results imply that (at least part of) the multilingual advantage is rooted in better access to the recently learned words because the training procedure ensured the same level of learning across groups. A similar pattern emerged in a recent study by Blumenfeld and Adams (2014). In that study, no difference was observed between Spanish-English bilinguals and English monolinguals on a nonverbal sound-to-symbol mapping task, which required mapping of tones to symbols based on pitch, timbre, and duration.…”
Section: Adultssupporting
confidence: 83%
“…Such effects have been documented in both adults (Bogulski et al (in p r e p a r a t i o n ) ; K a u s h a n s k a y a & M a r i a n , 2 0 0 9 a ; Kaushanskaya et al, 2013;Wang & Saffran, 2014) and children (Kalashnikova et al, 2014;Kaushanskaya et al, 2014). Further, experience with cross-language competition that improves the ability to manage specific cross-language interference has been suggested for adults (Bartolotti & Marian, 2012;Blumenfeld & Adams, 2014;Bogulski et al (in preparation). Finally, changes in the weight given to cues in the learning environment (such as enhanced reliance on pragmatic cue) appear to transfer to the novel word learning task in children (Brojde et al, 2012).…”
Section: Childrenmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous findings suggest that bilingual learning advantages may be domain-specific and limited to linguistic context that had previously been encountered by the individual (e.g., Kaushanskaya and Rechtzigel, 2012;Antoniou et al, 2014;Blumenfeld and Adams, 2014;Hirosh and Degani, 2017). The current findings are consistent with this literature.…”
Section: Summary Future Directions and Conclusionsupporting
confidence: 83%
“…E. Potter, T. Wang, J. R. Saffran / Cognitive Science 41 (2017) Another possibility is that the improvements stemmed from the process of learning a new language, not specifically from the sound properties of Mandarin. Knowledge of multiple languages has been proposed to have many cognitive benefits including enhanced implicit learning (e.g., Bartolotti et al, 2011;Klein, 1995;Kov acs & Mehler, 2009), cognitive control (e.g., Bialystok, 1999;Dijkstra & Van Heuven, 1998;Green, 1998;Green & Abutalebi, 2013), flexibility (e.g., Blumenfeld & Adams, 2014;Liu & Kager, 2014Prior & MacWhinney, 2010), and selective attention (e.g., Bialystok, 2001; Sebasti an-Gall es, Albareda-Castellot, Weikum, & Werker, 2012). However, there is currently a great deal of debate about both the existence of a domain-general "bilingual advantage," and if there is such an advantage, how it relates to individuals' linguistic experiences (e.g., Duñabeitia et al, 2014;Hilchey & Klein, 2011;Kaushanskaya & Prior, 2015;Paap & Greenberg, 2013;Yang, Hartanto, & Yang, 2016).…”
mentioning
confidence: 99%